Development of E-Modules on Shirt Making for Phase F Students of the Fashion Design Program at SMK Widya Praja Ungaran - Hidayah, Chincyn; Kusumastuti, Adhi (Universitas Negeri Semarang, 2025)
The results of observations of practical shirt-making lessons at SMK Widya Praja Ungaran revealed several problems, including slow achievement of learning objectives, students' lack of understanding of sewing techniques, incomplete learning media that are still based on the 2013 Curriculum, and the absence of e-modules integrated with the Merdeka Curriculum Phase F. In addition, most of the students' products did not meet the minimum passing grade of 75. This study aims to develop an e-module for shirt making, determine its feasibility, and assess its practicality. The method used is research and development with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. A questionnaire was used as a research instrument to collect data. The feasibility of the e-module was assessed by three subject matter experts and three media experts. The validation results showed that the e-module obtained a feasibility percentage of 91.67% from subject matter experts and 96.05% from media experts, both of which were classified as highly feasible. The practicality of the e-module was assessed by 21 students in class XI DPB 1. The appearance aspect scored 85.24% (very practical), the material presentation aspect scored 84.05% (practical), and the benefit aspect scored 82.31% (practical), with an average practicality of 83.86% (practical). Thus, the developed e-module is highly feasible and practical for use as a learning medium for shirt-making material for students in the Fashion Expertise Program Phase F.